ICTR basic document and case law - International Criminal Tribunal for Rwanda (Arusha : United Nations Publications, 2009)
ICTR basic document and case law database is a fully searchable coll ection of documents pertaining to the International Criminal Tribunal f or Rwanda and it is offered as a reference tool for legal professionals , law students, historians, and the general public.
Produced for ICTR by Metatorial Services, Inc. and Resource online, compiled by ICTR legal library.
Rwanda
256 MB RAM
Mac OS 10.2.8 or higher
Windows xp or vista
Monitor capable of displaying 1024 x 768
Keywords: United Nations; Criminal law -- Cases